Implementation of Digital Governance in State Administrative Law in The Village Government System - Lutter Ariestino; Agus Prasetia Wiranto (Jurnal Hukum Khaira Ummah, 2026)
The development of information technology is driving the transformation of government administration down to the village level through the implementation of digital governance. In the context of State Administrative Law, the digitalization of village government is a crucial instrument for improving the quality of public services, transparency, and accountability of village officials. However, its implementation still faces various challenges, both in terms of regulations, human resource capacity, and technological infrastructure. This study aims to analyze the implementation of digital governance in the village government system from the perspective of State Administrative Law, as well as to identify obstacles and necessary strengthening efforts. The research method used is normative juridical with a statutory and conceptual approach, through an analysis of regulations related to village government and electronic-based government systems. The results show that the implementation of digital governance at the village level has a sufficient legal basis, but has not been optimal due to limited access to technology, low digital literacy among village officials, and the lack of comprehensive regulatory harmonization. Furthermore, the implementation of digital systems also raises potential legal issues, such as the protection of public data and the risk of maladministration. From the perspective of State Administrative Law, the implementation of digital governance must remain based on the principles of legality, accountability, transparency, and the General Principles of Good Governance (AUPB). Therefore, it is necessary to strengthen policies, increase the capacity of village officials, and develop equitable digital infrastructure to realize effective, efficient, and equitable village governance.